Translation and the climate crisis: Attending to the local in a global emergency - Şebnem Susam-Saraeva (Encounters in Translation)
Discourse on the climate crisis is intrinsically dependent on and intertwined with the concept of translation. The term is used in distinct but interrelated senses in the relevant literature. The first, reflected in the term “knowledge translation”, generally refers to the dissemination of research findings to stakeholders and the general population. The second, closely related sense of translation concerns the rendering of scientific knowledge into effective action rather than merely disseminating it. These two interrelated meanings account for the bulk of references to translation in climate crisis discourse. Finally, reference is also made in climate crisis discourse to the more familiar but less acknowledged understanding of translation as rendering research papers, children’s literature addressing eco-anxiety, and other written material into different languages, as well as interpreting in international climate summits. This contribution analyzes these different uses of the concept of translation in climate crisis discourse and discusses their implications. The analysis is supported by examples from scholarly texts and news media, and the aim is to shed light on the workings of climate crisis discourse through the lens of translation. I argue that a renewed focus on the local through a foregrounding of interlingual translation—the least explored sense of translation in this literature—may help address some of the issues currently faced by scientists and policy makers.A synopsis of this article can be found here.